Effect of Red Ginger and Lemongrass Decoction on Blood Pressure in Hypertensive Elderly - Muhammad Rizman Akmal; Dewi Siti Oktavianti; Yenni Malkis; Gaung Eka Ramadhan (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Background: Hypertension is a common chronic disease in the elderly and can lead to serious complications such as stroke, heart failure, and visual impairment. Globally, hypertension affects approximately 1.28 billion adults, with only a small proportion achieving adequate control. Therefore, alternative non-pharmacological therapies are needed. This study aimed to determine the effect of a combination of boiled red ginger and lemongrass water on blood pressure in elderly patients with hypertension. Methods: This study used a quasi-experimental design with a pretest–posttest approach without a control group. The study was conducted in RT 02 RW 07 Pondok Kacang Timur, South Tangerang City. A total population of 50 hypertensive patients was identified, with 32 elderly respondents selected using consecutive sampling. Data were collected using a sphygmomanometer, observation sheets for blood pressure measurement, and intervention checklists. Ethical approval was obtained, and all participants provided informed consent. Data were analyzed using the paired t-test. Results: The primary outcome showed a decrease in blood pressure after the intervention. The mean systolic blood pressure decreased from 170.53 mmHg to 155.50 mmHg, and diastolic pressure decreased from 85.72 mmHg to 80.86 mmHg. Statistical analysis using the paired t-test revealed a significant effect, with a p-value of 0.001 (p < 0.05). These findings indicate that the combination of boiled red ginger and lemongrass water significantly reduces blood pressure in elderly hypertensive patients. Conclusion: This study contributes to the understanding of non-pharmacological management of hypertension by demonstrating the effectiveness of a combination of boiled red ginger and lemongrass water in reducing blood pressure. The findings provide practical insights for community-based nursing interventions. Future research is recommended to include control groups and larger sample sizes to strengthen the evidence.